Between the Critique of Socialism and Childhood Nostalgia: The Memory of Soviet Era in the Life Stories of the 1970s Generation - Šutinienė, Irena (Sociologija. Mintis ir veiksmas, 2020)
The article examines the autobiographical memory of the 1970s generation about the Soviet era. This generation, born in 1970–1979, is interesting for research because of its socialization in two different social and political systems: its childhood and adolescence date back to the Soviet period, while the beginning of adulthood coincides with the collapse of socialism and the restoration of democracy. Based on an analysis of life stories of the 1970s generation, the article explores features of memory of this generation, how it corresponds to the discourse of autobiographical memory of the Soviet era, as well as the generation’s role in the intergenerational transmission of Soviet-era family memory.
Keywords: generation; memories of Soviet era; life story; identity